FABRICATION OF A SCREW-RETAINED HYBRID PROSTHESIS FOLLOWING TREATMENT OF PERI-IMPLANT DEFECTS: A CASE REPORT - Bebek Serra OĞUZ-AHMET; Gülsüm SAYIN-ÖZEL; Hilal USLU TOYGAR (Journal of Istanbul University Faculty of Dentistry, 2016)
The etiology of marginal bone loss around osseointegrated implants is primarily based on the biomechanical and/or microbial factors. If stresses and strains around dental implants under functional loading conditions are expected to exceed the physiologic tolerance thresholds of the alveolar bone, the fixed hybrid prosthesis might be a more reliable treatment of choice instead of fixed metal ceramic restorations. The purpose of this article is to report the 1-year follow-up of the periodontal and prosthetic rehabilitation of a patient who has presented with symptoms of peri-implantitis due to incorrectly planned implant supported fixed metal ceramic bridge which was later replaced with screw-retained hybrid prosthesis following the treatment of peri-implant defects. Treatment helped to maintain patient’s self-confidence and comfort, as well as favorable masticatory function. Rehabilitation with screw retained hybrid prosthesis is an ideal treatment of choice for maxillomandibular skeletal discrepancies.